The Cassiopeia Filament: A Blown Spur of the Local Arm - Xuepeng Chen; Li Sun; Jiancheng Feng; Shiyu Zhang; Weihua Guo; Xiaoyun Xu; Yang Su; Yan Sun; Shaobo Zhang; Xin Zhou; Zhiwei Chen; Qing-Zeng Yan; et al. (The Astronomical Journal, 2022)
We present wide-field and high-sensitivity CO(1–0) molecular line observations toward the Cassiopeia region, using the 13.7 m millimeter telescope of the Purple Mountain Observatory. The CO observations reveal a large-scale highly filamentary molecular cloud within the Galactic region of 132.°0 ≥ l ≥ 122.°0 and −1.°0 ≤ b ≤ 3.°0 and the velocity range from approximately +1 to +4 km s ^−1 . The measured length of the large-scale filament, referred to as the Cassiopeia Filament, is ∼390 pc. The observed properties of the Cassiopeia Filament, such as length, column density, and velocity gradient, are consistent with those synthetic large-scale filaments in the inter-arm regions. Based on its observed properties and location on the Galactic plane, we suggest that the Cassiopeia Filament is a spur of the Local arm, which is formed due to the galactic shear. The western end of the Cassiopeia Filament shows a giant arc-like molecular gas shell, which extends in the velocity range from roughly −1 to +7 km s ^−1 . Finger-like structures, with systematic velocity gradients, are detected in the shell. The CO kinematics suggest that the large shell is expanding at a velocity of ∼6.5 km s ^−1 . Both the shell and finger-like structures outline a giant bubble with a radius of ∼16 pc, which is likely produced by the stellar wind from the progenitor star of a supernova remnant. The observed spectral line widths suggest that the whole Cassiopeia Filament was quiescent initially until its west part was blown by the stellar wind and became supersonically turbulent.